Institutional role conflict in the digital age: The case of diabetes management at school - Cassidy Puckett; Jenise C. Wong; Sloan Talbot; Hyojin Jennifer Min; Nora Chokr (Elsevier, 2023)
As the prevalence of pediatric diabetes grows and new technologies to manage diabetes emerge, there is increasing concern about consistency in health management across institutional settings, particularly in schools. While much is known about barriers at school, there are still gaps in understanding the institutional dynamics that shape health management in this setting. Using focus groups with 19 youth with type 1 diabetes (T1D) and applying institutional role theory, we find healthcare providers' recommendations conflict with school rules and norms, making it difficult to enact both the "sick role" and the "student role." These conflicts elicit negative responses from teachers and peers and stigmatize youth with T1D in school. Caregiver involvement often heightens rather than ameliorates conflict and teachers do not intervene in effective ways. Ultimately, youth must manage conflicts and stigma. By reframing challenges in health management as institutional role conflict, this paper contributes to sociological research by highlighting the importance of institutional roles, especially beyond healthcare. More broadly, the study suggests health research and policy should investigate how to better align institutional roles-rather than relying on youth and their families-to support health management of chronic illnesses across institutional settings.